Probable Haemoglobin Lepore Trait: A Rare Haemoglobinopathy Case Report from Bangladesh - Ferdous, Nira; Islam, Md Nazrul; Mustakim, Abu Talha (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Hemoglobin Lepore is one of the rare structural variations of hemoglobin (Hb) that arises from unequal crossing over between the δ and β globin genes. Hb Lepore heterozygous is clinically similar to people with mild thalassemia. Here we reported a 32-years-old male febrile patient diagnosed incidentally as a rare haemoglobin Lepore trait. J Bangladesh Coll Phys Surg 2026; 44: 60-63